HAK ATAS KEKAYAAN INTELEKTUAL SEBAGAI HARTA PAILIT DALAM HUKUM KEPAILITAN INDONESIA - Johnson Sahat Maruli Tua (to-ra, 2019)
Abstract Intellectual property can be in the form of exclusive patents, copyrights, brands, industrial designs, trade secrets and other rights that are part of an intellectual property regime. This exclusive intellectual property right is often the main asset owned by the bankrupt debtor or at least something valuable. In addition, Law No. 37 of 2004 concerning Bankruptcy and PKPU does not explain in detail whether the said assets are assets in the form of objects or material rights, because the law only regulates excluded assets or assets that cannot be made bankrupt assets. The Receiver who intends to administer and settle the intangible bankrupt assets such as IPR has always found it difficult to assess the assets. Keywords: intellectual property, assets, bankruptcy